Business Design and Implementation: Feasibility Study of Almond Chic Fashion Business in Yogyakarta - Lathifatunnisa (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research aims to answer the problems of people around the author who like Muslim fashion with vintage, casual and modern models, but which can still be used for a long time or is timeless. Almond Chic business development involves preparing marketing, operational, financial and human resource management plans. The marketing plan includes promotional strategies using social media platforms. The operational plan includes the product design process, raw material selection, and distribution to consumers. Financial plans focus on managing funds. Some of the challenges faced in implementing this business include marketing strategies that are not yet optimal, target markets that are not yet broad, and business implementation that is not in accordance with the planned schedule. This implementation report covers the entire period of 12 months since the initial design of the business idea began.